Deteksi Gejala Gangguan Jiwa Emosional dengan SRQ-20 pada Ibu Hamil: Contoh dari Sulawesi Selatan - Muhammad Rachmat; Fira Wati; Hasnaeni Hasnaeni; Sabaria Manti; Andi Hasliani; Hasnita Hasnita; Uliarta Marbun; Elvita Bellani; Devintha Virani; Muh. Ikhsan; Tanti Asrianti; Muliati Hidayat; Sitti Andriani Anwar (Sarana Ilmu Indonesia (salnesia), 2022)
The maternal health condition in Indonesia still requires special attention in terms of prevention and management of mental-emotional disorders. Meanwhile, the Indonesia Basic Health Research in 2013 results show that the prevalence of mental-emotional disorder was approximately 6% in each of the different provinces. This study aims to detect the prevalence of mental-emotional disorders symptoms in pregnant women and examine the relations with age, education, occupation, number of children ownership, MUAC (Mid-Upper Arm Circumference), and blood pressure. This is an analytical observational study conducted using a cross-sectional design on pregnant women that participated in antenatal examination visits to health facilities. The location was 60 Private Delivery Centers, 244 Public Health Centers, and 259 Hospitals. The sampling site was carried out in three different places, which focused on three areas of South Sulawesi in Makassar, Maros, and Pangkep. The pregnant woman within the age range of 20-35 years shows 71,3% with a p-value=0,080 having mental-emotional disorder symptoms and 71,5% of mothers with less than two children predominantly experienced mental-emotional disorders symptoms with a p-value=0,078. Hence, it is important to address this issue because the mental and emotional problems in pregnant women can potentially lead to adverse effects, both for the women and the baby.